Product Development in Drumstik ( moringa oleifera lam.) - Minonti pait (Department of Processing Technology, College of Agriculture, 2006)
The present investigation entitled “Product development in Drumstick (Moringa oleifera Lam.)” was carried out at the Department of Processing Technology, College of Agriculture, Vellayani, Thiruvananthapuram during the period 2005-2006. The objective of the study was to develop and standardize new products, to evaluate the quality and shelf life of the new product and to assess the consumer acceptance of the new products. Four products namely Dried pulp, Pulp powder, Dried pieces of fruits and Bottled pieces in brine had been developed and standardized. All the products were evaluated based on biochemical, shelf life and organoleptic qualities at the time of preparation as well as during storage. Ascorbic acid content in all the four products including three dried products and one bottled product were found to decrease with increase in storage period. Ascorbic acid content was found to be highest in dried pulp when stored in glass bottles, as compared to other three. All other biochemical quality attributes viz., fibre, fat, protein, vitamin A and total carbohydrate were found to decrease with increase in storage period in all the four products developed. Fibre, fat and total carbohydrate content were found more in all the three dried products than those in fresh drumstick fruits. But in case of bottled fruit pieces in brine it was found to be more or less similar to that of fresh one. Bottled fruit pieces in brine had high vitamin A content as compared to all other dried products. Regarding the storage studies and organoleptic quality, all the three dried products viz., dried pulp, pulp powder, dried pieces of fruits remained in good condition for upto six months, if properly packed. bottled fruit pieces in brine were good only upto four months. So the lowest shelf life was found to be for bottled fruit pieces in brine. Dried pulp was found more acceptable with regard to appearance, colour, flavour, taste and texture which is followed by pulp powder and dried pieces of fruits among the dried products. But after reconstitution dried pieces of fruits were found more acceptable. Bottled fruit pieces in brine were more acceptable with regard to appearance, colour and taste. The organoleptic qualities in all the four products decreased with increase in storage period. From the above study it is concluded that under-exploited crops like drumstick especially drumstick fruit can be utilized to develop many value added products like dried pulp, pulp powder, dried pieces of fruits and bottled fruit pieces in brine. And suitable packaging material should be developed in order to make these products to last long to make it attractive to the consumer.